The Problem of Physical Education of Pupils of 7-9 Forms in the Family - Koval’chuk, Hennadiy (Pedagogical Discourse, 2012)
The article examines the problem of physical education of teenagers in the modern family. The author reveals the potential possibilities of improving of the family impact onto the physical development of 7-9th-form pupils.